2019
DOI: 10.1177/0284185119826538
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution vessel wall magnetic resonance imaging of carotid and intracranial vessels

Abstract: Carotid and intracranial imaging play an essential role in the comprehensive evaluation and prevention for stroke patients. High-resolution vessel wall magnetic resonance imaging (HR VW-MRI) has been applied in carotid and intracranial arteries with optimal ability in displaying the features of various vascular diseases. Recent advanced MRI techniques can not only help in the differential diagnosis of vascular diseases but can also provide information on pathogenesis exploration of underlying mechanisms, follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 90 publications
0
6
0
1
Order By: Relevance
“…HR-MR imaging can accurately evaluate the vessel lumen, wall, and course; it can provide information on the degree of inflammation of the wall and the collateral circulation and distinguish lumen blood stasis and thrombus distal to the occlusion. 35,36 In this study, the HR-MR imaging characteristics of patients with successful recanalization included a tapered stump, less secondary collateral circulation, reversed distal ICA flow at the level of petrous segment or below, more lipid-rich necrotic core, less calcification volume, shorter lesion length (for proximal occlusion), and lumen iso-or hypointensity and larger lumen area (for distal occlusion). Multivariate analysis showed that shorter lesion length and less calcification volume (for proximal occlusion) and reversed distal ICA flow at the petrous segment or below and larger lumen area (for distal occlusion) were independent predictors of successful recanalization.…”
Section: Discussionmentioning
confidence: 98%
“…HR-MR imaging can accurately evaluate the vessel lumen, wall, and course; it can provide information on the degree of inflammation of the wall and the collateral circulation and distinguish lumen blood stasis and thrombus distal to the occlusion. 35,36 In this study, the HR-MR imaging characteristics of patients with successful recanalization included a tapered stump, less secondary collateral circulation, reversed distal ICA flow at the level of petrous segment or below, more lipid-rich necrotic core, less calcification volume, shorter lesion length (for proximal occlusion), and lumen iso-or hypointensity and larger lumen area (for distal occlusion). Multivariate analysis showed that shorter lesion length and less calcification volume (for proximal occlusion) and reversed distal ICA flow at the petrous segment or below and larger lumen area (for distal occlusion) were independent predictors of successful recanalization.…”
Section: Discussionmentioning
confidence: 98%
“…RFCs occurred in one-fifth of the BA plaques with moderate to severe stenosis (50–99%). For other intracranial arteries, such as the MCA, RFCs was hard to visualize by 3.0 T HR-MRI [ 14 ] due to the different geometry. The diameter of the BA is larger than that of the MCA; the shape of the BA is a relative straight line [ 15 ]; and the BA has more cisternal space when compared with the MCA [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…VW-MRI has an added aspect when diagnosing arterial dissection, as it contributes direct visualization and characterization of the wall of the vessel (17,19,(29)(30)(31)(32). A study conducted on arterial dissection found an intimal flap on luminal imaging (CTA, MRA, or DSA) in 16% of patients while on VW-MRI it was found in 42% (33).…”
Section: Discussionmentioning
confidence: 99%